The Big Five Personality Traits Indonesia Investor during the Covid-19 Pandemic - Werner Ria Murhadi; Bertha Silvia Sutejo; Phan Thá»‹ Há»“ng XuÃ¢n (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This study aims to determine the effect of the big five personality traits on financial risk tolerance and investment decision. The context of this research occurs for investors in Indonesia during the covid-19 pandemic period. The approach taken in this study is to use a quantitative approach method by distributing questionnaires to respondents who have become investors in Indonesia. Five independent variables measure a person's personality: extraversion, openness to experience, conscientiousness, and emotional instability, and two dependent variables are financial risk tolerance and investment decision. The results of this study prove that Personality traits extraversion, Intellect, and conscientiousness positively affect the level of financial risk tolerance. While personality traits of agreeableness and emotional instability negatively and significantly affect investors' financial risk tolerance levels. This research also provides results that financial risk tolerance positively affects investment decisions. This research has contributed to developing investor behavior theory which has yet to be widely carried out in Indonesia. The research shows that the big five personality impacts an investor's financial risk tolerance. Finally, this will have an impact on the investment decisions that an investor will make.